Interaction between arbuscular mycorrhizal fungi and soil microbial populations in the rhizosphere - Ike-Izundu, Nnenna Esther (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2008)
This study examined the rehabilitation potential of AM fungi with organic and inorganic fertilisers under pot and field trial conditions as well as their interaction with rhizospheric organisms and specific functional groups. In addition, the study highlighted the effects of land-use management on AM fungal populations in soil and the mycorrhizal status of some selected plants from one of the study sites. The study focussed on two sites that differ in operational activities and these included a mined area that was to be rehabilitated and a commercial farming site. A pot trial was conducted using an overburdened soil resulting from kaolin clay mining. Pots were seeded with Cynodon dactylon and treated with either Organic Tea or NPK (3:1:5) fertiliser, with or without AM fungal inoculum. The compatibility of these fertilisers with AM fungi was assessed by plant growth and percentage root colonisation. Maximum shoot height and plant biomass were observed at the 28th week with NPK (3:1:5) fertiliser supporting mycorrhizal colonisation by 80%. The result indicated the potential of AM fungi to be used in rehabilitation with minimal phosphate fertiliser. Similarly, a field trial was set-up using 17 x 17 m[superscript 2] plots in the mining site that were treated with the same organic and inorganic fertilisers as well as with AM fungal inoculum in different combinations. The interaction between AM fungi and soil microbial population was determined using culture dependent and culture independent techniques. The culture dependent technique involved the use of soil dilution and plating on general purpose and selective media. The result showed that there was no change in the total culturable bacterial number in the untreated and AM fungal treated plots, while a change in species composition was observed in the functional groups. Different functional groups identified included nitrogen fixing bacteria, pseudomonads, actinomycetes, phosphate solubilisers and the fungal counterparts. Gram-positive bacteria were observed as the predominant phenotypic type, while nitrogen fixers and actinomycetes were the predominant functional groups. Species identified from each functional group were Pseudomonas fulva, Bacillus megaterium, Streptomyces and actinomycetales bacteria. Meanwhile, fungi such as Ampelomyces, Fusarium, Penicillium, Aspergillus, Cephalosporium and Exserohilium were identified morphologically and molecularly. Furthermore, the mining site had a significantly higher bacterial number than the farming site thereby indicating the effects of land-use management on culturable bacterial numbers. The culture independent technique was carried out by cloning of the bacterial 16S rDNA and sequencing. Identified clones were Bradyrhizobium, Propionibacterium and Sporichthya. A cladogram constructed with the nucleotides sequences of identified functional species, clones and closely related nucleotide sequences from the Genbank indicated that nucleotide sequences differed in terms of the method used. The activity and establishment of the introduced AM fungal population was determined by spore enumeration, infectivity assay, percentage root colonisation and assessment of glomalin concentrations. The results indicated that the two land use types affected AM fungal populations. However, the establishment of AM fungi in the farming site was more successful than in the mining site as indicated by the higher infectivity pontential. Selected host plants, which were collected around the mine area, were observed to be mainly colonised by AM fungi and these were identified as Pentzia incana, Elytropappus rhinocerotis, Euphorbia meloformis, Selago corymbosa, Albuca canadensis and Helichrysum rosum. These plant species were able to thrive under harsh environmental conditions, thereby indicating their potential use as rehabilitation host plants. Generally, the findings of this study has provided an insight into the interaction between arbuscular mycorrhizal fungi and other soil microorganisms in two fields with differing land use management practices.
Keywords: Mycorrhizas; Mycorrhizal fungi; Vesicular-arbuscular mycorrhizas; Soil microbiology; Rhizosphere; Revegetation; Restoration ecology